Assessing the Protective Effects of Benoxacor, Fenclorim, Melatonin, and 2,4,6-Trichlorophenoxyacetic Acid Against Herbicide Injury in Tomato - Tabata Raissa de Oliveira; Antonio Augusto Correa Tavares; Shaun Broderick; Taghi Bararpour; Te Ming Tseng (HortTechnology)
Safeners protect crops by enhancing their ability to metabolize various compounds, including herbicides. They increase a crop’s tolerance to herbicide damage, activating herbicide-metabolizing proteins, and aiding in their detoxification. This study aimed to investigate the chemical effects of safeners in tomato cultivation and focus on injury reduction and tissue protection. The experiment followed a randomized factorial design (5 × 4) with four replications repeated twice. We evaluated the effects of herbicides dicamba, 2,4-D, metribuzin, and sulfentrazone (diluted to 1% of the recommended field rate) and safeners benoxacor, fenclorim, melatonin, 2,4,6-T, and an untreated control. Safeners were applied to the seeds before sowing, and herbicides were applied as a foliar spray 25 days after sowing. Visual injury was evaluated 7, 14, and 21 days after application (DAA). Biomass measurements were taken 21 DAA. Results showed that preconditioning tomato seeds with 2,4,6-T, melatonin, and fenclorim 7 DAA significantly decreased injury by 25, 25, and 23%, respectively. Moreover, applying melatonin, benoxacor, and 2,4,6-T 21 DAA led to significantly greater dry biomass, which increased by 1.5, 1.42, and 1.44 times, respectively, compared with the control. This research provides valuable insights into the chemical effects of benoxacor, fenclorim, 2,4,6-T, and melatonin safeners in tomato cultivation. The findings demonstrate the potential for preconditioning tomato plants with 2,4,6-T, melatonin, and fenclorim to reduce herbicide injury. Additionally, melatonin, benoxacor, and 2,4,6-T stimulated growth, increasing tomato dry biomass. Understanding plant defense mechanisms and the protective effects of safeners against herbicide damage contributes to developing effective weed management strategies.